Correlation between relaxometry and diffusion tensor imaging in the globus pallidus of Huntington's disease patients - Syka, Michael; Keller, Jiří; Klempíř, Jiří; Rulseh, Aaron M; Roth, Jan; Jech, Robert; Vorisek, Ivan; Vymazal, Josef (PloS one, 2015)
Huntington's disease (HD) is an inherited neurodegenerative disorder with progressive impairment of motor, behavioral and cognitive functions. The clinical features of HD are closely related to the degeneration of the basal ganglia, predominantly the striatum. The main striatal output structure, the globus pallidus, strongly accumulates metalloprotein-bound iron, which was recently shown to influence the diffusion tensor scalar values. To test the hypothesis that this effect dominates in the iron-rich basal ganglia of HD patients, we examined the globus pallidus using DTI and T2 relaxometry sequences. Quantitative magnetic resonance (MR), clinical and genetic data (number of CAG repeats) were obtained from 14 HD patients. MR parameters such as the T2 relaxation rate (RR), fractional anisotropy (FA) and mean diffusivity (MD) were analysed. A positive correlation was found between RR and FA (R2=0.84), between CAG and RR (R2=0.59) and between CAG and FA (R2=0.44). A negative correlation was observed between RR and MD (R2=0.66). A trend towards correlation between CAG and MD was noted. No correlation between MR and clinical parameters was found. Our results indicate that especially magnetic resonance FA measurements in the globus pallidus of HD patients may be strongly affected by metalloprotein-bound iron accumulation.
Keywords: Male; bazální ganglia; železo; Huntingtonova nemoc; Adult; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Aged; dospělí; zobrazování difuzních tenzorů; mužské pohlaví; senioři; Huntington Disease; lidé; Diffusion Tensor Imaging; ženské pohlaví; Iron; Basal Ganglia; Humans; Globus Pallidus; DNA Repeat Expansion; globus pallidus; expanze repetic DNA; Female; lidé středního věku; Middle Aged